Common Fixed Point for a Contractive Mapping via (α, β, ψ)-Admissibility in b-metric space - K . Maheshwaran; R . Jahir Hussain; D . Dhamodharan (Ratio Mathematica, 2022)
In this paper, we establish the concept of a common fixed point theorem for a pair of self-mappings (R,S) in b-metric space via (α, β, ψ )-Admissibility type contractive condition. And illustrate an example.